Surgical outcome in chronic syndesmotic injury: A systematic literature review. Issue 5 (October 2019) - Krähenbühl, Nicola; Weinberg, Maxwell W.; Hintermann, Beat; Haller, Justin M.; Saltzman, Charles L.; Barg, Alexej
Highlights: Few articles exist assessing the surgical outcome of chronic syndesmotic injuries. Retrospective case series are the most frequently used study design. Many different operative techniques are used to address chronic syndesmotic injuries. Good clinical outcomes were evident in the most studies. Abstract: Background: Chronic injuries of the distal tibio-fibular syndesmosis often present with non-specific clinical and radiographic findings. If chronic instability to the distal tibio-fibular syndesmosis is verified, various reconstruction options are available. The purpose of this article is to give a systematic review of current surgical treatment options in patients with chronic syndesmotic injury. Methods: Three major medical databases were searched from inception through December 12, 2017: PubMed, ScienceDirect, and SpringerLink. Studies were included if they were original research studies which assessed the outcome of patients treated surgically for chronic syndesmotic instability. Only studies written in English were considered. The following data were extracted from each study: number of patients and ankles included, average patients' age, gender, study design, preoperative examination, time between the initial injury and the operation, postoperative follow-up time, operative technique, complication rates, and clinical outcome. The modified Coleman Score was used to assess the methodologic quality of the included studies. Results: Seventeen (17) studies were included. All studies were retrospective or prospective case series. Each study was performed at a single center. In general, good functional outcomes and low complication rates were reported. The American Orthopaedic Foot and Ankle (AOFAS) score was most frequently used outcome tool to measure postoperative outcomes. The quality of the included studies was overall satisfactory. Conclusions: A few studies have reported on the operative outcomes after treating chronic syndesmotic instability. Several different techniques were used to treat this problem. The quality of current studies is overall satisfactory but could be improved with larger patient numbers and prospective analysis. Recognition of this clinical entity as an identifiable and treatable cause of ankle pain requires vigilant clinical investigation. Level of evidence: Level IV; Systematic Review of Level IV Studies.